Design and validation of a prognostic index of death from COVID-19: a prospective cohort - Alexis Álvarez Aliaga; Julio César González Aguilera; Alexis Suárez Quesada; Andrés José Quesada Vázquez; Liannys Lidia Naranjo Flores; Adonis Frómeta Guerra (Revista Habanera de Ciencias Médicas, 2024)
Introduction: COVID-19 caused high morbidity and mortality worldwide due to the lack of effective treatment and timely recognition of individuals with worse prognosis.